2005
DOI: 10.1007/s11255-004-7970-4
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Ureteric Injuries: Incidence, Aetiological Factors and the Effect of Early Management on Subsequent Outcome

Abstract: In our Unit, the incidence of significant iatrogenic ureteric injuries has shown a decline over a 5-year period. We attribute this trend to the prophylactic use of "J" stents or ureteric catheter placement and good surgical technique during major abdomino-pelvic surgeries in our hospital. Endourological procedures are the commonest causes of ureteric injuries. Prompt diagnosis and institution of appropriate corrective surgical procedures often result in a very satisfactory outcome in about 94% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 14 publications
8
89
0
3
Order By: Relevance
“…quency of complications varies between 0.5% and 10% in the literature (1)(2)(3). Ureteral avulsion is the most serious complication and occurs in 0-0.5% patients (4).…”
Section: Original Papermentioning
confidence: 99%
“…quency of complications varies between 0.5% and 10% in the literature (1)(2)(3). Ureteral avulsion is the most serious complication and occurs in 0-0.5% patients (4).…”
Section: Original Papermentioning
confidence: 99%
“…25,29,33,34 Overall success rates range from 48% to 88% for balloon dilation, 55% to 85% for endoureterotomy, and 91% to 97% for conventional open surgery. 35 In our series of 10 patients, laparoscopic management of early (6) and late (4) detected ureteral injuries was accomplished in all cases but one (success rate, 90%) despite the fact that it was a uretero-uretero anastomosis, ureterolysis, or ureteral reimplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Awadi et al 5) found that the length of hospitalization, incidence of urinary leak, adhesions, and sepsis were significantly higher in the delayed diagnosis group.…”
Section: Intraoperative Ureteral Injury Identificationmentioning
confidence: 98%
“…Although may occur at any segment of the ureter, it most often occurs distally near the takeoff of the IMA or at the pelvic brim. Al-Awadi et al 5) reported 82 cases of IUI over a period of 4 years. Anatomical locations were 65%, 20%, and 15% for distal, mid, and proximal ureteral injury, respectively.…”
Section: Prevention Of Iatrogenic Ureteral Injury In Colorectal Surgerymentioning
confidence: 99%
See 1 more Smart Citation